Relationship Religious Coping with Smoking Behavior of Adolescent Students Islamic Boarding School Al Amin Paciran Lamongan - Rizal Faisal Basri; Peni Perdani Juliningrum; Iis Rahmawati (Nursing and Health Sciences Journal (NHSJ), 2021)
Smoking behavior in adolescents is caused by a lack of self-control, stress and imitating their peers. Religious coping is expected to reduce maladaptive behavior in adolescents. This study aims to determine the Relationship of Religuisity Coping with Smoking Behavior of Adolescent Students Islamic Boarding School Al Amin Paciran Lamongan. Research method uses correlational quantitative with a cross-sectional approach. Sampling used a total sampling method, the total sample was 32 respondents. The results of this study were 17 respondets had positive religiosity coping, 15 respondets had negative religiosity coping. Regarding smoking behavior, there were 16 respondets who did not smoke, 7 respondets adolescents had light smoking behavior, 4 respondets adolescents had moderate smoking behavior and 5 respondets had heavy smoking behavior. The results of the variable correlation test using the Kendal tau test obtained the Asymp.Sig (2-tailed) value of 0,000 where the value is less than <0.005 The correlation coefficient value is 0.654. Conclusion that there is a relationship between coping religiosity with smoking behavior of adolescent students islamic boarding school Al Amin Paciran Lamongan. Hopefully the results can be used to reduce smoking behavior in adolescents